2009
DOI: 10.1073/pnas.0905314106
|View full text |Cite
|
Sign up to set email alerts
|

Precuneus shares intrinsic functional architecture in humans and monkeys

Abstract: Evidence from macaque monkey tracing studies suggests connectivity-based subdivisions within the precuneus, offering predictions for similar subdivisions in the human. Here we present functional connectivity analyses of this region using resting-state functional MRI data collected from both humans and macaque monkeys. Three distinct patterns of functional connectivity were demonstrated within the precuneus of both species, with each subdivision suggesting a discrete functional role: (i) the anterior precuneus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

104
752
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 880 publications
(876 citation statements)
references
References 49 publications
104
752
3
Order By: Relevance
“…Margulies et al (20) reported that the precuneus in humans is functionally connected to the lateral frontal, posterior parietal, and occipital cortices. The precuneus is one of the most connected regions of the cortex, suggesting that it may serve as a hub in several cortical networks.…”
Section: Discussionmentioning
confidence: 99%
“…Margulies et al (20) reported that the precuneus in humans is functionally connected to the lateral frontal, posterior parietal, and occipital cortices. The precuneus is one of the most connected regions of the cortex, suggesting that it may serve as a hub in several cortical networks.…”
Section: Discussionmentioning
confidence: 99%
“…Granted, the use of animal models is somewhat limited because of interspecies differences in neuroanatomy (45,46). However, given the similarities in the connectivity profile between the monkey and human brain (47,48), macaque models will continue to serve as an indispensable tool for explicating general organizational principles of brain networks such as characterization of the directional transitions that axons make when entering or exiting gray matter (35,49,50). Insights from such studies may help improve the accuracy of tractography techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Recent R-fMRI studies have identified putative biomarkers of neuropsychiatric illness (12,(15)(16)(17)(18), provided insight into the development of functional networks in the maturing and aging brain (19)(20)(21)(22), demonstrated a shared intrinsic functional architecture (23) between humans and nonhuman primates (24,25), and delineated the effects of sleep (26), anesthesia (27), and pharmacologic agents on R-fMRI measures (28,29). Given the many sources of variability inherent in fMRI, the remaining challenge is to demonstrate the feasibility and utility of adopting a high-throughput model for RfMRI, commensurate with the scale used by human genetics studies to have the power to detect both single gene and combinatorial genetic and environmental effects on complex phenotypes.…”
mentioning
confidence: 99%